Numerical simulation of industrial die filling using the discrete element method. (22nd December 2015) - Tsunazawa, Yuki; Shigeto, Yusuke; Tokoro, Chiharu; Sakai, Mikio
Abstract: Die filling is an important aspect of powder molding in chemical engineering. The discrete element method (DEM) has been applied to simulations of die filling systems in the literature. In these simulations, the die has been modeled by simple shapes such as cylinders and cuboids. However, industries require modeling of complex die shapes in the computations. In addition, the existing DEM is problematic from the viewpoint of industrial applications, since complexly shaped dies might not be modeled by existing technologies. To solve this problem, the signed distance function (SDF) model is applied to the DEM simulation (DEM/SDF) and the DEM/SDF approach is validated for arbitrarily shaped dies. Focusing on macroscopic powder flow, simulation results are compared with experimental results, and good agreement is confirmed for the spatial distribution of velocity, the projection areas of the shoe, and the final mass of filling particles. Therefore, the adequacy of the DEM/SDF model is newly demonstrated in the die filling system; i.e., the DEM/SDF method is shown to be an effective method for the numerical simulation of particle flow into arbitrarily shaped dies. Graphical abstract: Highlights: The signed distance function (SDF) model was employed to the DEM simulation. In this study, the DEM/SDF model is newly applied to arbitrarily shaped dies. The macroscopic flow in the simulation corresponds to that in the experiment. Adequacy of the DEM/SDF model is validated in the case of a die filling system. The DEM/SDF model is shown to be effective to industrial die filling systems.